2013
DOI: 10.1186/1746-6148-9-224
|View full text |Cite
|
Sign up to set email alerts
|

Lung progenitors from lambs can differentiate into specialized alveolar or bronchiolar epithelial cells

Abstract: BackgroundAirways progenitors may be involved in embryogenesis and lung repair. The characterization of these important populations may enable development of new therapeutics to treat acute or chronic lung disease. In this study, we aimed to establish the presence of bronchioloalveolar progenitors in ovine lungs and to characterize their potential to differentiate into specialized cells.ResultsLung cells were studied using immunohistochemistry on frozen sections of the lung. Immunocytochemistry and flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, the presence of BASC in humans and sheep has not been firmly established (95). Cells displaying some features of BASC have been described in sheep (72, 96) but their significance in OPA tumourigenesis remains unclear.…”
Section: Opa As a Model For Studying Pulmonary Adenocarcinoma Tumourimentioning
confidence: 99%
“…However, the presence of BASC in humans and sheep has not been firmly established (95). Cells displaying some features of BASC have been described in sheep (72, 96) but their significance in OPA tumourigenesis remains unclear.…”
Section: Opa As a Model For Studying Pulmonary Adenocarcinoma Tumourimentioning
confidence: 99%
“…Moreover, the concentrations of TGF-β by Western blot analysis ( Figure 1D ) and of the anti-asthmatic factor SOX2 by IHC ( Figure 1E ), were significantly lower in gestationally SS-exposed lungs. SOX2 is a pluripotent transcription factor in bronchoalveolar progenitors, which promotes the Club cells to express Clara-cell secretory protein (CCSP) and surfactant protein-C (SP-C) ( 54 ). CCSP and SP-C are suppressed by gestational SS ( 10 ) and reduced SOX2 and CCSP levels are associated with higher risk of asthma ( 55 ); humans and mice deficient in CCSP, exhibit airway hyperresponsiveness ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reviews have described the different lung stem cells identified, mainly characterized in humans and mice [ 15 , 22 25 ]. Descriptions of lung stem cells in other medium and large mammals are still very sparse, except in our work on the identification of ovine bronchioloalveolar progenitors with dual differentiation potential [ 26 ].…”
Section: Endogenous Stem/progenitor Cells Of the Lungmentioning
confidence: 99%
“…To date the vast majority of in vitro lung models are developed from mouse and human tissues, with protocols published, describing the method used to isolate and cultivate primary adult lung epithelial cells alone or in coculture, as monolayers, as a polarized epithelium (2D) or at the air–liquid interface (ALI) [ 39 ]. Few data are available on other model species, especially those of agronomic interest, but we can point to several papers on porcine [ 40 ], bovine [ 41 44 ], equine [ 45 ] and ovine [ 26 , 46 ] lung cells. Primary adult differentiated lung epithelial cells remain difficult to isolate due to their low turn-over.…”
Section: Mimicking the Lung In Vitromentioning
confidence: 99%